SISTEM PARKIR BERBASIS WEB + IOT PROJECT KIT SERI RFID DI HASIM TEKNIK KARAWANG - Bias Yulisa Geni; Okto Kurnia (KH. A. Wahab Hasbullah University, 2021)
Advances in technology today require humans to increase their effectiveness and efficiency in various ways. Basically the purpose of creating a tool is to help human work to be more effective and efficient. Thus, humans are expected to function in a relatively short time, especially when it comes to safety. The parking lot is a medium that is used as a way of getting in and out of vehicles. Anticipating some problems in the parking lot, for example: losing parking papers, losing cars in parking lots, and preventing illegal parking at high levels. Then we need an automatic parking door system. This final project aims to build a prototype of an IoT-based automated parking system. This project is a simple parking simulator with a microcontroller device programmed to use the Arduino idea. Hardware integrated with mysql database and run by simple web. The automated parking system is designed using nodemcu lolin, expansion board, 16x2 + i2c LCD adapter, mini mp3 dfplayer, 0.5 watt ohm earbuds, infrared sensor, rfid rc522 and SG90 servo motor. Infrared sensor detects vehicle, rfid receives input by tapping card and then gives output to i2c and web. Furthermore, the output from the LCD goes to the service motor which opens and closes the parking door, and the dfmp3 player, as well as the speaker which makes a sound when the card is tapped. This prototype automatic parking system can provide access and close automatic parking doors which saves time and effort. It can be concluded that the prototype of this IoT automatic parking system can be used as a guide for the development of a better technology.